Design of a Distribution Network Power Quality Monitoring System based on Metering Automation Systems and its Application - Feng Tianrui; Ouyang Sen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
According to the situation that almost all the power quality systems (PQM) focus on the transmission network rather than the distribution network (DN), a distribution network power quality monitoring system (DNPQMS) based on metering automation systems is proposed in this paper. This DNPQMS can take full advantage of the power data collected by the existing intelligent terminals that set throughout the DN. The DNPQMS is divided into three parts, including equipment layer, data layer and application layer. The equipment layer consists of power quality monitoring devices, including the power quality monitoring device based on dual-CPU platform and intelligent terminals of other manufacturers. The data layer completes the power data storage and integrated that collected by the intelligent terminals. The application layer completes the day-to-day maintenance and management of the system as well as a number of advanced applications. The verification of the DNPQMS by application is presented at the end of the paper. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1450